The exiles of Herta Müller - Acosta Gómez, Luis A. (Revista de Filología Románica, 2012)
Certainly Herta Müller became a largely recognized writer ever since the conferment of de Nobel Price in the year 2009. This article deals with a critic approach to the signification of her texts. There are first of all observed the press German and Romanian reactions about the conferment of the price. Thereafter is analyzed her first in Romania publicized text Niederungen and the latter evolution and confirmation of a peculiar writing already in the German exil and at the last the most important and characteristic of all her production Atemschaukel. Under a sociological point of view this contribution it deals the evolution of her literary texts by considering both exiles she has experienced where the historic memory becomes an essential guideline.